The Shifts in Meaning in the Film Translation of The Captain (中国机长, 2019) - Dea Rachmawati; Octi Rjeky Mardasari; Dudy Syafruddin (Journal of Chinese Language and Culture Studies, 2025)
This study aims to describe the types of translation meaning shifts and the forms of meaning shifts that dominate in the film The Captain 中国机长 (2019). Meaning shifts occur due to cultural differences, language conventions, or social contexts between Mandarin and Indonesian. The research method used was qualitative analysis involving data reduction, data presentation, and conclusion drawing. Data was taken from the film's subtitles and analysed using M.D.S. Simatupang's theory of meaning shifts, including generic to specific shifts, specific to generic shifts, and cultural differences. The results of the study show that meaning shifts caused by cultural differences dominate over shifts from generic to specific and specific to generic, with eight data points out of a total of 16 analysed. The researcher hopes that this study can help translators, especially those in translation classes, to gain a deeper understanding of translation theory, types of meaning shifts in different contexts, and expand their vocabulary and knowledge of culture so that they can produce more in-depth analysis.